1999
DOI: 10.1038/12175
|View full text |Cite
|
Sign up to set email alerts
|

Continual remodeling of postsynaptic density and its regulation by synaptic activity

Abstract: A postsynaptic density (PSD) protein, PSD-95, was tagged with green fluorescent protein (GFP-PSD-95) and expressed in cultured hippocampal neurons using recombinant adenoviruses. GFP-PSD-95 was selectively localized to excitatory postsynaptic sites. Time-lapse fluorescence imaging of hippocampal neurons revealed that >20% of GFP-PSD-95 clusters turned over within 24 hours. The appearance rate of clusters was higher than the disappearance rate, and this difference accounted for the gradual increase of the clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
201
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 231 publications
(221 citation statements)
references
References 41 publications
19
201
0
1
Order By: Relevance
“…1a). PSD-95-GFP clusters are a reliable marker for the postsynaptic structure [34][35][36] . Therefore, spines containing PSD-95-GFP (PSD-95-GFP-( þ ) spines) can be classified as more differentiated spines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a). PSD-95-GFP clusters are a reliable marker for the postsynaptic structure [34][35][36] . Therefore, spines containing PSD-95-GFP (PSD-95-GFP-( þ ) spines) can be classified as more differentiated spines.…”
Section: Resultsmentioning
confidence: 99%
“…Synapse turnover is regulated by both activitydependent and -independent pathways 32,34,49 . Synapses can still be generated without activity-dependent processes, but the process of synapse stabilization may be selectively affected 50 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that CaMKII and PSD-95 puncta are dynamic [3,4,7,17,34] but how these dynamics relate to the formation, loss and stabilization of synaptic contacts where both pre-and postsynaptic structures can be followed simultaneously has not been studied. To begin to understand how PSD-95 and CaMKII are distributed at stable and labile AD connections, we first assessed their static localization rates to presynaptic sites in fixed cultures, using either sites of AD contact (figure 1a) or the excitatory presynaptic marker VGlut1.…”
Section: Resultsmentioning
confidence: 99%
“…Presumably neurons must form and then maintain a population of stable contacts with specific synaptic partners in order to ensure proper circuit function, but the molecular mechanisms that underlie this process of synapse stabilization are still poorly understood [1,2]. Further, the ability of a synapse to remain stable is complicated by the recent demonstration that many synaptic proteins are highly dynamic and turn over in both activity-dependent and independent manners [3][4][5][6][7]. Here, we used time-lapse imaging of synapse formation in cultured neocortical neurons to examine the dynamics of association of Ca 2þ /calmodulin-dependent protein kinase II (CaMKII) and postsynaptic density-95 (PSD-95) with sites of axon-dendrite (AD) contact, in order to assess how the localization and amount of these proteins correlates with changes in contact turnover.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation